Teaching Collegiality in Mexican Primary School: An Analysis of Its Practices - Martínez-Cruz, Efren (2017)
Teaching collegiality in the Mexican primary school is influenced by a global dynamic that forms a complex school culture, with singular educational practices that have been established over time. A qualitative investigation of ethnographic character was conducted by using the case study modality. The case consisted of 13 professionals in charge of the primary education management. The techniques used to collect data were participant observation, semi-structured interview and analysis of documents. Through an inductive research process, empirical categories of analysis were constructed to finally produce an interpretative text that identified some practices of teacher collaboration; these practices are described and analyzed in this article. Among the main findings, it was identified that what motivates the teaching staff to collaborate with others has to do with resolving practical and immediate situations with preciseness; so, the school can continue to function with «a sense of normality». It was also confirmed that the time for teaching collegiality is not scheduled; then, the teachers often consume their students’ recess time, and even the management staff extends that time to develop different meetings related to providing several types of information.